Exogenous myristate promotes the colonization of arbuscular mycorrhizal fungi in tomato - Liu, Xiaodi; Feng, Zengwei; Zhang, Wei; Yao, Qing; Zhu, Honghui (Frontiers in Plant Science, 2023)
Arbuscular mycorrhizal fungi (AMF) can establish symbiotic associations with the roots of the most terrestrial plants, thereby improving the tolerance of the host plants to biotic and abiotic stresses. Although AMF cannot synthesize lipids de novo, they can obtain lipids from the root cells for their growth and development. Recent study reveals that AMF can directly take up myristate (C14:0 lipid) from the environment and produce a large amount of hyphae in asymbiotic status; however, the effect of environmental lipids on AM symbiosis is still unclear. In this study, we inoculated tomato (Solanum lycopersicum) with AMF in an in vitro dual culture system and a sand culture system, and then applied exogenous myristate to the substrate, in order to explore the effect of exogenous lipids on the mycorrhizal colonization of AMF. We investigated the hyphae growth, development, colonization of AMF, and examined the gene expression involved in phosphate transport, lipid biosynthesis and transport. Results indicate that exogenous lipids significantly stimulated the growth and branching of hyphae, and significantly increased the number of hyphopodia, mycorrhizal colonization of AMF, with arbuscular abundance and intraradical spores or vesicles being the most promoted. In contrast, exogenous myristate decreased the growth range and host tropism of the germ tubes, and largely inhibited the exchange of nutritions between symbionts. As a result, exogenous myristate did not affect the plant growth. This study suggests that lipids promote mycorrhizal colonization by enhancing the growth and development of AMF hyphae and increasing their contact opportunities with plant roots. To the best of our knowledge, this is the first report that lipids promote the colonization of AMF. Our study highlights the importance in better understanding the roles of environmental lipids in the establishment and maintenance of AM symbiosis, and thus in agricultural production.